Single implant‐supported crowns in the aesthetic zone: patient satisfaction with aesthetic appearance compared with appraisals by laypeople and dentists. Issue 10 (26th May 2014) - Fava, Joseph; Lin, Mark; Zahran, Mohammed; Jokstad, Asbjorn
Abstract Objective To appraise the patients' satisfaction with aesthetic outcomes following an implant restoration in the anterior maxilla as compared to appraisals made by dentists and laypeople. Material and methods Randomly selected patients (n = 116) restored with an implant‐retained crown in the anterior maxilla were invited to rate their satisfaction with aesthetic outcomes using a questionnaire containing seven criteria, each graded from excellent to poor. Projected images of the patient smiles were appraised by dentists (n = 8) and laypeople (n = 6) using the same assessment criteria in a room setting. In addition, the laypeople judged the same cases on printed 10 × 15 cm photographs in a separate setting. Jemt papilla scores, pink aesthetic score (PES) and white esthetic score (WES) were assigned by the dentists. Differences in the levels of satisfaction between the patient, and appraisals by the dentists and the laypeople were compared using non‐parametric statistical tests. Results Patients' opinions of their aesthetic appearance following the placement of a single implant‐supported crown in the aesthetic zone were in general very favourable. The laypeople were more critical than the dentists when the aesthetic outcomes were appraised on magnified images projected onto a screen. Laypeople became less critical when evaluating the aesthetic outcomes on printed photographs compared to appraisals on a screen. Patient satisfaction with their aesthetic appearance differed from dentists' and laypeople's appraisals. Conclusion Factors other than the actual aesthetic outcome itself appear to influence patients' satisfaction with their end results. Laypeople's appraisal is influenced by the magnification and method used for appraising the aesthetic outcomes.